1998
DOI: 10.1016/s0146-6380(98)00005-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel pathway of soil organic matter formation by selective preservation of resistant straight-chain biopolymers: chemical and isotope evidence

Abstract: A resistant soil organic residue, 'humin', has been analysed by solid-state 13 C-NMR and pyrolysis followed by molecular and 13 C determination of the pyrolysate alkane-alkene fraction. The results show the occurrence of highly aliphatic, straight-chain biopolymer material as a substantial part of soil organic matter. They confirm the hypothesis by which a part of soil organic matter can be formed by selective preservation of resistant highly aliphatic microbial polymers. This pathway comes in addition to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
1
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(105 citation statements)
references
References 21 publications
7
95
1
2
Order By: Relevance
“…However, the molecular structure of humic substances being poorly known and still a matter of debate (14,15), other processes may explain how humification takes place. Indeed, several studies suggest that a substantial part of humin is made of lipidic components (8,11,(15)(16)(17). Here, we report the identification of n-alkanes, steroids, isoprenoid, hopanoids, and aliphatic biopolymers trapped in soil humin.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, the molecular structure of humic substances being poorly known and still a matter of debate (14,15), other processes may explain how humification takes place. Indeed, several studies suggest that a substantial part of humin is made of lipidic components (8,11,(15)(16)(17). Here, we report the identification of n-alkanes, steroids, isoprenoid, hopanoids, and aliphatic biopolymers trapped in soil humin.…”
Section: Introductionmentioning
confidence: 74%
“…Numbers refer to carbon numbers of n-alkanes and n-alkenes. Detailed procedures are reported elsewhere (16,17,24). A sample of maize crop soil (290 g) was thoroughly extracted with CHCl 3 -MeOH 3/1 v/v to remove free lipids, then with NaOH 0.1 M to remove fulvic and humic acids.…”
Section: Linear Alkanesmentioning
confidence: 99%
“…This was confirmed for an agricultural soil by Quenea et al (2006), who observed old-forest-and fungi-derived odd long-chain alkanes based on compound-specific isotope analysis and lipid distribution patterns. Possible pathways of in situ genesis of n-alkanes in soils are the reduction of nalkenes and n-alcohols, the decarboxylation of bacterial nfatty acids, and the degradation of biopolymers containing aliphatic side chains (Lichtfouse et al, 1998a). Nevertheless, based on the large number of studies in which typical higherplant-derived patterns of lipids are reported and used in soils (Table 1), including indicative ACL and CPI values, microbial input of longer chain length straight-chain lipids generally does not seem to be a major factor compared to directplant-derived input in the topsoil Bai et al, 2009).…”
Section: Microbial Inputmentioning
confidence: 99%
“…3), also indicated that the patterns of polysaccharide C (C-O bonds at 1035 cm . It should be kept in mind, however, that the nature of the clay-bound organic matter may vary with clay surface chemistry (Greenland 1965;Jardine et al 1989;Golchin et al 1995;Lichtfouse et al 1998;Kahle et al 2003;Zimmerman et al 2004). We were not successful in exploring other clay minerals or amorphous oxides that may have a very strong control on C stabilization through surface interactions (Mikutta et al 2006).…”
Section: ¡1mentioning
confidence: 99%